Data from: Lightning damage facilitates beetle colonization of tropical trees - Parlato, Brady; Gora, Evan; Yanoviak, Stephen (Dryad, 2020)
Lightning is a common agent of disturbance in many forest ecosystems.
Lightning-damaged trees are a potentially important resource for beetles,
but most evidence for this association is limited to temperate pine
forests. Here, we evaluate the relationship between lightning damage and
beetle colonization of tropical trees. We recorded the number of beetle
holes on the trunks of trees from 10 strike sites (N = 173
lightning-damaged trees) and 10 matching control sites (N = 137 control
trees) in Panama. The trunks of lightning-struck trees had 370% more
beetle holes than control trees. The abundance of beetle holes increased
with increasing total crown dieback among both control and
lightning-damaged trees, and with larger tree diameter among
lightning-struck trees. Beetle holes also were more abundant in trunk
sections of lightning-damaged trees located directly below a damaged
section of the crown. The results of this study suggest that lightning
damage facilitates beetle colonization in tropical forest trees and
provide a basis for investigations of the effects of lightning-caused
disturbance on beetle population dynamics and assemblage structure.
Keywords: Forest Entomology; Tropical Insect Ecology